Analysis of differences in fingerprint patterns of achieving students with ordinary students - Arsya Gusnita, Arsya; Divi Andini, Divi; S. Syamsurizal, Syamsurizal (Genetikawan Muda Indonesia, 2024)
Fingerprints are one of the parts examined on dermatoglyphs. Fingerprints are images on the skin of the fingertips that are formed from the embryo and are maintained without changing. This research method uses a descriptive method with a Purposive Sampling technique which is carried out by taking fingerprint samples from students who were ranked 1-5 and students who were ranked in the bottom 5 in the class at SMA N 3 Payakumbuh and MAN 2 Agam. The percentage of students' fingerprint patterns is calculated by comparing the number of each fingerprint patterns with all the fingerprints of students at two schools with two sample group. Based on the data in Table 1, the percentage of fingerprint patterns for group of outstanding students: loop 57%, whorl 26.6% and arch 16%. Ordinary group of students with a loop percentage of 60%, whorl 26.2% and arch 13.8%. From these data it can be seen that the loop fingerprint pattern is always higher than the whorl and arch respectively sample group. This shows that with different levels of achievement, fingerprint patterns form observed fingers did not show significant differences. Even though the pattern in get both Loop patterns, but the percentage of each pattern is different.